Pengembangan Profesionalitas Pendidik Menurut Ki Hajar Dewantara - Diah Rahayu Isnaini; Naning Puji Lestari; Mohammad Romadlon Habibulloh (Pascasarjana Universitas Qomaruddin, 2024)
The government's efforts to develop the teaching profession into a strong and respected profession on e-par with other professions can be seen with the promulgation of Law Number 14 of 2005 concerning Teachers and Lecturers Who Practice the Teaching Profession to develop legal protection. The government has made efforts to improve the professionalism and qualifications of teachers and increase the requirements for higher teacher education from schools to universities. Ki Hajar Dewantara has many ideas that have been implemented in Indonesian education. One of his most famous ideas is the concept of items, nirokke, and namambahi, known as Tri-N. If translated into Indonesian, these three words mean paying attention, imitation adding. These three elements have characteristics that are very suitable for the development of creativity. Ki Hadjar Dewantara's educational philosophy is to instill culture in children. The concept of this learning is Tri No, namely watching, eating, and korokke. Watching (cognitive), watching here is passive with all the five senses. Niteni (affective) is marking, studying, paying attention to what the five senses perceive, and nirokke (psychomotor) is imitating positive things to prepare for facing children's development. This article aims to provide alternative solutions to increase teacher professionalism through various aspects, one of which is according to Ki Hajar Dewantara. One important factor that has a big influence on the quality of education is the school principal as an educational leader. School principals are required to be able to lead organize and manage the implementation of teaching and learning programs that are organized to achieve educational goals. As well as all elements in education such as educators, students, the community environment and so on who help each other in the learning process to achieve educational goals.